Regional and cell type-specific variations in tonic GABAergic inhibition. - Lee, Vallent. (2017)
Abstract: BACKGROUND: The diversity of GABAA receptor subunits and their configurations during subunit assembly produce a variety of receptors with different functional properties. Variations in subcellular localization, GABA binding affinity, and pore kinetics give rise to two classes of GABAergic conductance—phasic and tonic—with heterogeneity across brain regions and cell types. The precise roles of tonic versus phasic GABAergic signaling are only beginning to be uncovered. METHODS: Here we used a novel floxed Gabrd mouse model to selectively remove the extrasynaptic delta subunit–containing receptors that mediate tonic inhibition from specific cell types, and studied the impact from the cellular level to circuits to behavior in physiological and pathological contexts. RESULTS: Three areas of investigation were explored: (1) Removal of the delta subunit from excitatory principal neurons was expected to increase neuronal excitability and result in greater susceptibility to pharmacologically induced seizures. However, dentate gyrus granule cells proved resistant to complete removal of the delta subunit, suggesting the importance of tonic inhibition in controlling hippocampal excitability. (2) Removal of tonic inhibition from interneurons of the hippocampus resulted in greater inhibitory drive onto principal neurons. This suppression of hippocampal excitability produced a phenotype that showed protection against seizures, but also exhibited deficits in learning and memory. (3) Tonic GABAergic conductance in CRH neurons of the paraventricular nucleus in the hypothalamus plays a role in modulating the body's physiological response to stress. Because the chloride gradient is flipped during acute stress, removing the delta subunit from CRH neurons blunted the release of corticosterone and diminished stress-related behaviors. CONCLUSIONS: Taken together, our studies have sampled a bit of the variety in the roles of tonic GABAergic conductance across brain regions and cell types. Further experiments with other genetic tools will allow greater focus into more specific cell types and neural circuits. The floxed Gabrd mouse should prove a useful tool for future investigations.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Neuroscience.; Advisor: Jamie Maguire.; Committee: Chris Dulla, Stephen Moss, and Leon Reijmers.; Keyword: Neurosciences.